Identifying Critical Elements of Treatment: Examining the Use of Turn Taking in Autism Intervention. (September 2014) - Rieth, Sarah R.; Stahmer, Aubyn C.; Suhrheinrich, Jessica; Schreibman, Laura; Kennedy, Joanna; Ross, Benjamin
Evidence-based treatments for autism spectrum disorders (ASD) are comprised of components that identify therapist behavior necessary to implement the treatment with integrity. Some components are shared across approaches from diverse theoretical backgrounds. One component included in several interventions that has not been researched in isolation is turn taking, or the manner in which the therapist facilitates back-and-forth interaction with the child. The current study used an alternating treatments design to examine the efficacy of four types of turn taking. Six children, ages 30 to 39 months, received behavioral treatment while therapists systematically varied the nature of the turn taking component. Children's responses were behaviorally scored to examine differences based on turn condition. Consistent patterns of behavior were found across children. Results suggest that the optimal type of turn is dependent on developmental level and target skill. Implications for treatment of ASD and future research directions are discussed.